Aplikasi Filosofi Tri Hita Karana dalam Konsep Perencanaan Lansekap Gereja Katolik Santa Maria Immaculata, Tabanan - WARDANI, IVANNA WISNU; SUDARSANA, A.A. GEDE DALEM; SARWADANA, SANG MADE (Jurnal Arsitektur Lansekap; Vol.1, No.1, April 2015, 2015)
ABSTRACT Tri Hita Karana as Site Plan Concepts of Santa Maria Immaculata Catholic Church Tabanan Landscape Santa Maria Immaculata Catholic Church Tabanan (SMICCT) landscape has been developed for sufficient the user activities.  There is no particular site plan concept, therefore SMICCT garden is not well ordered.   This research aims to apply Tri Hita Karana (THK) as SMICCT site plan concept, to adjust THK with the user activities and apply the garden elements that unify the characters of THK.  The results of this research showed that SMICCT landscape needs to be structured the garden to create a space and provide atmosphere which contains the activities of users.  THK as SMICCT site plan concepts are used to categorize the space based on the user activities, and to choose garden elements in creating the atmosphere of space on the SMICCT landscape.   Keywords: cultural inculturation , tri hita karana , site plan